The Influence of Use of Local Financial Management Information System in Order To Create Transparency and Accountability Financial Management - Wildoms Sahusilawane (AFEBI Accounting Review, 2016)
This research aims to examine the effect of Regional Financial Management Information System in achieving Transparency and Accountability. The research population involves the head of administration, chief financial officer, treasurer and staff in Ambon and Tual City in Maluku Province with total number are 125 respondents, This research uses purposive sampling as research sample in which it fulfils total of 114 resondents.The questionnaire was tested by using reliability test and validity test. Then, it was continued with classic assumption test contained of multicollinearity test, normality test, and heteroskedastisity test.After that, there was hypothesis test and discussion.The result showed that that variable the use of Local Financial Management Information System had showed positive and significant impact on the transparency of financial management while the effect of the use of Local financial management information system showed no significant effect on the financial management accountability.Keywords: Local Financial Management Information System, Transparency, Accountability